ANALISIS KEUNTUNGAN DAN SKALA USAHA PERKEBUNAN KELAPA SAWIT GERBANG SERASAN (Studi di Kecamatan Gunung Megang Kabupaten Muara Enim) - Ranika Tiwi Wijayanti; Bagio Mudakir (Diponegoro Journal of Economics, 2013)
Palm oil is one of plantation commodities, which is potential to have the market share in both domestic and international market. The prospect encourages palm oil farmers of Gerbang Serasan to increase their production with the purpose to achieve maximum profit. However, the farmers of Gerbang Serasan are faced to the problem of limited capital, as the production input price is getting higher, and the price of palm oil is uncertain. The aims of the research are to recognize the effects of the factors affecting business profit, maximum profit condition, and the return to scale condition of Gerbang Serasan's palm oil plantation in the Sub District of Gunung Megang. This research used primary data obtained from direct interview to the respondents. The respondents examined were all palm oil farmers of Gerbang Serasan (81 farmers). The analysis model applied was the profit function model of Cobb-Douglas, applied the method of Ordinary Least Squares (OLS) processed by SPSS Program version 16. The research results show the costs of NPK fertilizer and nitrogen (urea) fertilizer, the number of productive trees has significantly positive effect on profit, herbicide cost has significantly negative effect on profit, on the other hand, weighing and carry cost statistically have no effect on profit. The return to scale is in the condition of Increasing Return to Scale (IRS).